2020
DOI: 10.1088/1361-6587/aba4bd
|View full text |Cite
|
Sign up to set email alerts
|

Impurity transport in the pedestal of H-mode plasmas with resonant magnetic perturbations

Abstract: Experiments on DIII-D show that resonant magnetic perturbations (RMPs) reduce the impurity confinement time in the H-mode pedestal below that of naturally ELMy plasmas. STRAHL modeling of discharges with aluminum laser blow off (LBO) injection show increased diffusion in the pedestal of H-mode discharges with RMPs. The increased diffusion from the RMPs provides improved impurity control compared to the naturally ELMy discharges and prevents the buildup of impurities near the edge of the plasma. Tungsten LBO in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The sum of information from various diagnostics provides a more localized likelihood and improves the ill-posed conditions. References [15,16] combined charge exchange spectroscopy (CXRS), vacuum ultraviolet spectroscopy, and soft x-ray measurements and inferred the D and v profiles that are consistent with all the diagnostics.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The sum of information from various diagnostics provides a more localized likelihood and improves the ill-posed conditions. References [15,16] combined charge exchange spectroscopy (CXRS), vacuum ultraviolet spectroscopy, and soft x-ray measurements and inferred the D and v profiles that are consistent with all the diagnostics.…”
Section: Introductionmentioning
confidence: 85%
“…Several references [11,[15][16][17] have already reported impurity transport studies by using the Bayesian formalism. In these approaches, the probability distribution for the D and v profiles, which is called the prior, is first defined without considering the data.…”
Section: Introductionmentioning
confidence: 99%
“…where Φ (1) and Φ (2) are the numerical solutions calculated twice and the difference is evaluated in the domain D. In the case of Fig. 8, this difference is 1.9 × 10 −2 .…”
Section: Theoremmentioning
confidence: 99%
“…When numerical simulation methods are used to study impurity transport in the edge region of a quasi-steady tokamak plasma, the three-dimensionality of the magnetic field in the edge region should be considered. Currently, static resonant magnetic perturbations (RMPs) are commonly used to mitigate or suppress edge-localized modes (ELMs) in tokamak plasma [1][2][3]. Victor et al [2] reported that "RMPs are effective at controlling impurity build up in the pedestal region, regardless of ELM suppression."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation